Evaluation of social protection adaptive capacity friendliness for sustainable human security among teen youths in a peri urban area of Akwa Ibom State, Nigeria (2023)
This study evaluated the teen youth responsiveness towards sustainable socio-economic health security intervention communication, the responsiveness index of the respondents was estimated and how significant variations in teen youths responsiveness across their characteristics were ascertained. The study was conducted in the Itu Local Government Area of Akwa Ibom State, Nigeria. The target population of the study was all youths between the ages of 14 and 25 years. A multi-stage sampling technique was used and a total of200 respondents were sampled to generate the needed data that were subjected to descriptive and inferential statistics. The results revealed that 93.5% of the teen youths were aware of the threat of HIV/AIDs issues to the sustainable socio-economic-health status of households as 32.5% had the courage to visit the VCT center to ascertain their status. It was surprising that only 25%> knew that the VCT services were confidential. Overall, about 34% of the teen youths had a responsiveness index that was considered high and friendly to call to know HIV/AIDs status; and adopt voluntary counseling and testing to promote zero HIV spread in the region. With regards to sources of variation in teen-youths responsiveness index, the majority of the personal characteristics of the respondents; sex, number of household income earners, father’s level of education, and household size, were statistically not significant variables even though there were considerable variations in the mean index of teen-youths responsiveness to HIV/AIDs VCT across their factors. The variable: age showed statistical significance among its age range categories. As the age range increased, it revealed a higher index of teen-youth responsiveness, which suggested that maturity with advancement in age increases the consciousness of young adults to be careful and safe in society. Irrespective of the background characteristics of the respondents, their decision to stay safe was more of a personal decision to stay safe and healthy.